2009
DOI: 10.1002/esp.1729
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated flow erosion rates reduced through biological geotextiles

Abstract: Soil erosion by concentrated flow can cause serious environmental damage. Erosion-control geotextiles have considerable potential for reducing concentrated flow erosion. However, limited data are available on the erosion-reducing potential of geotextiles. In this study, the effectiveness of three biological geotextiles in reducing soil losses during concentrated flow is investigated. Hereto, runoff was simulated in a concentrated flow flume, filled with an erodible sandy loam on three slope gradients (13·5, 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…Also, similar results were found by Jankauskas et al (2008a,b) in Lithuania when used on road embankments. Smets et al (2009) found that rill and gully erosion can be controlled by means of biological geotextiles either on medium or steep slopes. Davies et al (2006) have also shown the use of geotextiles can be a positive strategy for soil and water conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, similar results were found by Jankauskas et al (2008a,b) in Lithuania when used on road embankments. Smets et al (2009) found that rill and gully erosion can be controlled by means of biological geotextiles either on medium or steep slopes. Davies et al (2006) have also shown the use of geotextiles can be a positive strategy for soil and water conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Their effectiveness is comparable to artificial materials tested at lower slopes (Chen et al, 2011). The selected materials also presented enhanced effectiveness with respect to alternative natural textiles, see, for instance Smets et al (2009Smets et al ( , 2011b. This behaviour may be also attributed to the experimental conditions (including natural rainfall), which did not favour concentrated erosion processes.…”
Section: Discussionmentioning
confidence: 75%
“…Significant studies have also entailed the preparation and testing of advanced textiles including innovative materials. Geotextile assessments have been conducted both in laboratory (Smets et al, 2009) and field conditions (Jankauskas et al, 2012); however, field-based observations more reliably replicate erosion and runoff mechanisms (Smets et al, 2011b). More recently, experimental observations have been coupled with soil erosion models to improve the performance of predictive tools (Smets et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that in the long run, by vegetation efforts along with cut slope and fill slope, soil loss can be reduced by at least 30% and this ratio can reach 90% [27]. As a precaution in the short term, and geotextile and blanket applications in slope have been reported to decrease soil loss [40] significantly and improve soil quality properties [41]. Also, soil properties affecting K value affect the soil loss in cut and fill slope through to the forest road [42].…”
Section: Scenario-based Recalculation Of Soil Loss Amounts In Slopes mentioning
confidence: 99%